Fundal height growth curve patterns of pregnant women with term low birth weight infants - Deeluea J; Sirichotiyakul S; Weerakiet S; Khunpradit S; Patumanond J (Dove Medical Press, 2014)
Jirawan Deeluea,1,2 Supatra Sirichotiyakul,3 Sawaek Weerakiet,4 Suthit Khunpradit,5 Jayanton Patumanond6 1Clinical Epidemiology Program, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 2Department of Obstetrics and Gynecology Nursing, Faculty of Nursing, Chiang Mai University, Chiang Mai, Thailand; 3Department of Obstetrics and Gynecology, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 4Department of Obstetrics and Gynecology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 5Department of Obstetrics and Gynecology, Lamphun Hospital, Lamphun, Thailand; 6Clinical Epidemiology Unit and Clinical Research Center, Faculty of Medicine, Thammasat University, Pathum Thani, Thailand Purpose: To investigate the patterns of fundal height (FH) growth curve in pregnant women with term low birth weight (LBW) infants compared with the standard FH growth curve for Thai women. Subjects and methods: A retrospective study was conducted at the four governmental general hospitals in the northern part of Thailand between 2009 and 2011. All data were obtained from antenatal records and labor registry. Serial FH measurements in centimeters of 75 pregnant women with term LBW infants were plotted against the standard FH growth curve for Thai women throughout pregnancy. Results: Six patterns of the FH growth curve were summarized: pattern I: FH below or around the tenth percentile throughout pregnancy (n=17, 22.7%); pattern II: FH below normal in early pregnancy, caught up with normal, then decelerated or stagnant (n=19, 25.3%); pattern III: FH normal in early pregnancy, then decelerated or stagnant (n=17, 22.7%); pattern IV: FH normal in early pregnancy, decelerated or stagnant, then caught up to normal (n=6, 8.0%); pattern V: FH normal throughout pregnancy except for the last visit (n=6, 8.0%); and pattern VI: FH normal throughout pregnancy (n=10, 13.3%). Conclusion: Patterns I–V may be used to recognize women who are likely to deliver term LBW infants from early pregnancy, during pregnancy, and on the day of admission for labor. Ultrasound evaluation is still recommended in cases with known risk factors that might be undetectable by FH, or in cases where FH measurement may be inaccurate. Keywords: fetal growth, pregnancy, antenatal care, screening